IMPLEMENTASI KEBIJAKAN TRANSPARANSI DAN AKUNTABILITAS PELAYANAN PUBLIK (STUDI DI PDAM KOTA BANDUNG) - Teni Listiani (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2019)
This research aims at identifying how transparent and accountable service policy is implemented at PDAM Bandung City from the perspectives of PDAM employees and its customers. The result demonstrate good responses from the PDAM employees. Meanwhile, ustomer’s responses reflect that the implementation of transparent and accountable service policy has yet to improve. To diminish the gap, it is necessary for PDAM Bandung City to set some measures to deliver its services in more transparent and accountable ways. The measures include the improvement orpersonnel’s competencies and professionalism.